A cross sectional study of polycystic ovarian syndrome among young women in Bhopal, Central India - Gupta, Mahesh; Singh, Daneshwar; Toppo, Manju; Priya, Angelin; Sethia, Soumitra; Gupta, Preeti (International Journal Of Community Medicine And Public Health, 2017)
Background: Polycystic ovarian syndrome (PCOS) is the most common endocrine disorder among women of reproductive age groups. It is one of the leading causes of poor fertility. Risk factors include obesity, not enough physical exercise, and a family history. Most studies in India report prevalence of PCOS as 9.13% to 36%. Behaviour and life style modifications are important part of treatment for PCOS. A number of cases in the community due to lack of awareness and proper guidance, it remains undiagnosed. Aim of this study was to find the prevalence of PCOS among the young females of Bhopal city. Thus, risk assessment in the form of a survey would be one of the strategies to identify this syndrome early so as to encourage young women to seek timely treatment and prevent its long term complications. Methods: Non comparative cross sectional study for duration of 8 month. Results: The prevalence of PCOS in this study was 8.20%. Among all the risk factors, BMI ≥25 (P value < 0.0001) and waist hip ratio ≥0.85 (<0.0001) were strongly associated with the presence of PCOS and Lack of awareness, there were in girls (78.4%). Conclusions: Women who were having BMI ≥25 and waist hip ratio ≥0.85 should be educated about its complications and should be advised weight loss. Girls who had irregularity of menses and signs of hyperandrogenism should be investigated and must be managed accordingly. Early diagnosis of PCOS and its prompt treatment will help the girls to improve quality of life.